2019
DOI: 10.15184/aqy.2019.170
|View full text |Cite
|
Sign up to set email alerts
|

Sedentism, pottery and inland fishing in Late Glacial Japan: a reassessment of the Maedakochi site

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The association we note between early pottery and aquatic resources appears to have deep cultural roots and extends over large parts of East Asia, including other parts of Late Glacial Japan (Craig et al, 2013) and the Lower Amur (Shoda et al, 2020), plus the Early Holocene of Japan (Lucquin et al, 2016a(Lucquin et al, , 2018, Korea (Shoda et al, 2017) and Sakhalin Island (Gibbs et al, 2017). In general, much of the earliest pottery in Japan appears to have involved mobile groups gathering seasonally to harvest fish runs, which would have diversified subsistence during periods of extreme cold (Morisaki et al, 2019), but may also have involved group feasts and other rituals, as has been suggested in other world regions (Taché and Craig, 2015). However, the aquatic relationship also persists into warmer periods of the Late Glacial (Craig et al, 2013), and more surprisingly, across the major climatic and environmental shifts between the Pleistocene and Holocene, when warmer climates and expanding broad-leaved forest cover would have provided abundant new plant and animal resources such as nuts and wild ruminants (Lucquin et al, 2018).…”
Section: Aquatic Resources and Early Pottery Use In East Asiamentioning
confidence: 73%
“…The association we note between early pottery and aquatic resources appears to have deep cultural roots and extends over large parts of East Asia, including other parts of Late Glacial Japan (Craig et al, 2013) and the Lower Amur (Shoda et al, 2020), plus the Early Holocene of Japan (Lucquin et al, 2016a(Lucquin et al, , 2018, Korea (Shoda et al, 2017) and Sakhalin Island (Gibbs et al, 2017). In general, much of the earliest pottery in Japan appears to have involved mobile groups gathering seasonally to harvest fish runs, which would have diversified subsistence during periods of extreme cold (Morisaki et al, 2019), but may also have involved group feasts and other rituals, as has been suggested in other world regions (Taché and Craig, 2015). However, the aquatic relationship also persists into warmer periods of the Late Glacial (Craig et al, 2013), and more surprisingly, across the major climatic and environmental shifts between the Pleistocene and Holocene, when warmer climates and expanding broad-leaved forest cover would have provided abundant new plant and animal resources such as nuts and wild ruminants (Lucquin et al, 2018).…”
Section: Aquatic Resources and Early Pottery Use In East Asiamentioning
confidence: 73%
“…Cooper’s Ferry occupation is associated with late upper Paleolithic (LUP) bifacial point-bearing sites in Hokkaido (figs. S12 and S13) ( 9 , 21 , 22 ). This LUP bifacial point tradition is preceded by a blade-point industry dating from ~32,000 to 20,000 cal yr B.P.…”
Section: Discussionmentioning
confidence: 99%